UNDERSTANDING THE QURAN HOLISTICALLY: INTERDISCIPLINARY STUDY OF THE LANGUAGE AND LINGUISTICS OF THE QURAN - Muh Barid Nizarudin Wajdi; Nur Iftitahul Husniyah; Victor Imaduddin Ahmad; Miftakhul Ilmi Suwignya Putra; Ahmad Muhtar Syarofi (Universitas Islam Malang, 2023)
This study aims to analyze the impact of the language used in the Quran on Islamic discourse, using qualitative research methods and content analysis of Quranic verses and scholarly literature. The study finds that the Quranic language's unique literary style and linguistic features contribute to its authority and persuasiveness, shaping Islamic discourse over time. Rhetorical devices, such as repetition and parallelism, add to the text's effectiveness. The study highlights the importance of understanding the Quranic language and its impact on Islamic theology, jurisprudence, and ethics, emphasizing the need for interdisciplinary research. By analyzing the linguistic and literary features of the Quran, scholars can gain a deeper understanding of the text's meaning and message and appreciate its continued relevance in contemporary times. This study contributes to the broader understanding of the role of language in shaping religious discourse and interpretation.